Alkali-Treated Pineapple Leaf and Water Hyacinth Fibers for PLA Biocomposites: A Review - Achmad Zakki Ardiansyah; Tri Hartutuk Ningsih; Vivi Aisah Fardilah; Anggra Fiveriati (Journal of Fibers and Polymer Composites, 2026)
Sustainable polymer composites require renewable reinforcements whose mechanical performance, processing feasibility, durability, and end-of-life behavior are supported by evidence. This review maps alkali-treated pineapple leaf fiber (PALF) and water-hyacinth-related materials for polylactic acid (PLA) and related biopolymer composites, focusing on interface modification, mechanical and flexural behavior, durability limitations, and application gaps. A PRISMA-style systematic mapping approach was applied using a corrected modular evidence-mapping strategy rather than one all-concept Boolean string. From a precompiled reference-summary dataset of 1,218 records, 50 studies were retained after residual duplicate checking, title-and-abstract screening, full-text eligibility assessment, and quality appraisal. Evidence was classified into direct PLA/PALF studies, WHF fiber-reinforcement studies, WHF filler or functional-additive studies, water-hyacinth biomass-to-PLA feedstock studies, alkali-treatment/interface studies, broader PLA/natural-fiber evidence, and methodological sources. PALF has stronger direct evidence in PLA matrices, including continuous-fiber 3D printing, layer-to-layer additive manufacturing, molding routes, and hybrid systems. WHF remains underexplored in PLA; current evidence mainly comes from WHF/HDPE, WHF/PBS, WHF/thermoplastic starch, WHF/epoxy, and feedstock-conversion studies. The quantitative extraction reports treatment conditions, fiber fractions, processing routes, tensile and flexural values, moduli, impact data, and percentage changes where available. Examples include flexural strength of 35.81 MPa and modulus of 5.28 GPa for alkali-treated coir/PALF/PLA, 132.75 MPa flexural strength for NaOH-treated jute-PALF/PLA, and flexural-strength gains of 15.86-98% across relevant systems. The proposed PLA/PALF/WHF hybrid is framed as a testable PALF-primary/WHF-secondary hypothesis requiring direct validation, standardized treatment, durability testing, LCA, and application-specific assessment.